2008
DOI: 10.1021/ac7022348
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Identification of Individual Leukemia Cells by Laser Trapping Raman Spectroscopy

Abstract: Currently, a combination of technologies is typically required to assess the malignancy of cancer cells. These methods often lack the specificity and sensitivity necessary for early, accurate diagnosis. Here we demonstrate using clinical samples the application of laser trapping Raman spectroscopy as a novel approach that provides intrinsic biochemical markers for the noninvasive detection of individual cancer cells. The Raman spectra of live, hematopoietic cells provide reliable molecular fingerprints that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 26 publications
6
154
2
2
Order By: Relevance
“…In addition, the eventual use of this technology in future clinical cell-based transplantations for purifying and enriching cell populations would obviously require similar cell sorting instrumentation. It is anticipated that optical tweezers [42][43][44] for cell manipulation and advanced nonlinear Raman techniques such as CARS [45,46] and stimulated Raman scattering (SRS) to enhance the weak Raman scattering signals will be important components in future Raman-based cell sorting systems. A study using CARS for stem cell characterization has been reported [46], the results of which were in agreement with the Raman studies discussed above.…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…In addition, the eventual use of this technology in future clinical cell-based transplantations for purifying and enriching cell populations would obviously require similar cell sorting instrumentation. It is anticipated that optical tweezers [42][43][44] for cell manipulation and advanced nonlinear Raman techniques such as CARS [45,46] and stimulated Raman scattering (SRS) to enhance the weak Raman scattering signals will be important components in future Raman-based cell sorting systems. A study using CARS for stem cell characterization has been reported [46], the results of which were in agreement with the Raman studies discussed above.…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…LDA has been used with Raman spectroscopy to create binary classification models to identify leukemia [484] and gastric dysplasia [438]. LDA can also be performed multiple times to create a multi-level classification model (i.e.…”
Section: Linear Discriminant Analysismentioning
confidence: 99%
“…Raman spectroscopy continues to push its frontier, enabling individual neoplastic cell identification, such as shown in the works of Chan et al (34,35). Owing to improved and advanced Raman techniques, Cell surface is a very important target in investigations focused on carcinogenesis processes.…”
Section: Raman Spectroscopy In Cancer Diagnosismentioning
confidence: 99%